The essentials of total fitness : exercise, nutrition, and wellness - Powers, Scott K. (Scott Kline), 1950-; Dodd, Stephen L. (Boston : Allyn and Bacon, 1997)
This book is about: Understanding health-related fitness and wellness; Fitness evaluation: self-testing; Improving flexibility; Nutrition, health, and fitness; ...
Keywords: Nutrition; Health; Physical fitness; Exercise; Physical fitness; Exercise; Nutrition; Health